Fostering adaptation to climate change among farmers in Pakistan: the influential role of farmers’ climate change knowledge and adaptive capacity - Mustafa, Ghulam; Alotaibi, Bader Alhafi (Frontiers in Sustainable Food Systems, 2024)
Introduction: Adaptation to climate change (ACC) is imperative to avoid deleterious consequences of climate change in agriculture. However, the uptake of adaptation measures has been slow among farmers because low adaptive capacity (AC) in developing countries, particularly in Pakistan. Therefore, farmers and their supporting institutions have been successful in introducing technological innovations to respond and adapt to environmental challenges. The study in hands intends to find the impact of farming technologies along with human, financial, social, physical, natural and climate information resources that support AC and hence ACC. Methods: The study collected that data from 360 farmers in Punjab through multistage random sampling technique. Binary logit model and odds ratio are used to find the factors affecting ACC. The study also utilizes correlation tests to show the correlation between each pair of variables we included in the analysis. Results: The results indicate that physical capital such as ownership of tube-well, transportation, sowing and harvesting tools by the farmers build farmers' AC and consequently determine the ACC such as change crop variety, change crop type, change planting dates, soil conservation, water conservation, and diversification. Findings also revealed that human capital (age, education, family size and labour), financial capital (off-farm employment, access on marketing of produce and agricultural credit), social capital (farmers-to-farmers extensions, access on extension services and membership of farm association) and natural capital (land ownership, tenancy status and location of farm) were pointedly related to farm households' ACC strategies. Odds (likelihood) of adaptation is more for farm technology users as compared to non-users. Discussion: The analysis of the study shows that the climate information resource amplifies the adaptation to climate change: technology allows farming to be much, much more efficient while climate change knowledge self-motivates farmers to adapt more ACC measures. Our findings provide evidence to provide credits and financial support for farming technologies that speed up the ACC in the long-run while in the short-run climate information should be spread among farming communities.